Overcoming Quiet Quitting by Reducing Role Ambiguity and Work-Leisure Conflict to Promote Decent Work - Priambodo, Ary; Putra, Okta Prihatma Bayu (Journal of Business & Applied Management, 2025)
In today’s era, workers are required to multitask to meet company and consumer expectations. This has the potential to create role ambiguity and work-leisure conflict. Both of these factors typically lead to employee resignation or disengagement. Considering the current competitive job market, workers tend to be “quiet quitter” rather than resign. This study aims to analyze the relation between role ambiguity, work-leisure conflict, and quiet quitting. This quantitative study used a questionnaire as a survey tool for respondents. The questions were adapted from previous studies. To determine the value of respondents’ answers, 5-point Likert scale was used. A total of 208 employees in Indonesia were selected using simple random sampling and served as the sample in the study. This research employs partial least squares structural equation modeling (PLS-SEM) and SmartPLS as analytical instruments. This study’s findings indicate that role ambiguity can affect work-leisure conflict and quiet quitting among employees, work-leisure conflict can affect quiet quitting, and mediate the relationship between role ambiguity and quiet quitting. This study’s findings enhance human resource management strategies to promote decent work by evaluating the role ambiguity and work-leisure conflict factors. This study’s limitations and recommendations for future research will be described in this study.